GEON Journal Vol 6 No 2 July December 2019 (GEON Journal (Management, Organizations and Business), 2019)
Compensation strategy as a job satisfaction tool; Regulations of the Patent and Trademark Law: a Mexican perspective; Customer service, service, product and price as determining variables of customer satisfaction in a service SME; Mobbing study at a higher education institution in Hidalgo; Proposals to strengthen the entrepreneurial culture in the municipalities of Puebla and Tlaxcala; Case study for the development and implementation of an environmental management system; Categorization of establishments according to the aggregate values ​​perceived by the consumer in socioeconomic levels 3 and 4 in Bogotá, Colombia; An analysis of the gender wage gap: case applied to a manufacturing company in Escobedo, Mexico; Management of observatories in the internationalization of Higher Education in Latin America; Is reading an important component of organizational culture in companies?
Keywords: compensation; patents; customer satisfaction; mobbing; entrepreneurial culture; enviromental management; consumer; salary gap; internationalization higher education; organizational culture